PENGARUH PEMBERIAN EKSTRAK DAUN MANGROVE (Rhizophora mucronata) DENGAN DOSIS YANG BERBEDA TERHADAP PERTUMBUHAN IKAN BANDENG (Chanos chanos) - Syakirin, M. Bahrus; Linayati, Linayati; Mardiana, Tri Yusufi; Agustin, Septianti (JARI : Jurnal Akuakultur Rawa Indonesia, 2023)
The purpose of this study was to identify the effect of giving Rhizophora mucronata mangrove leaf extract at different doses and to get the best dose in increasing the growth of milkfish. The research method was a completely randomized design with 4 treatments and 3 replications. The treatments used were: A, (control feed dose), B (administration of mangrove leaf extract at a dose of 1.5 mg/kg feed), C (administration of mangrove leaf extract at a dose of 1.7 mg/kg feed), D administration of mangrove leaf extract at a dose of 1.9 mg/kg of feed). The results showed that the highest growth rate was obtained in treatment C with a dose of 1.7 mg/kg of feed mangrove leaf extract, with an increase in biomass of 2.39 g while feeding was carried out for 30 days and weighing was carried out on the last day. The lowest growth was obtained in treatment A with control feed doses resulting in average growth of 1.5 g. Survival during the study results obtained 100% with a growth F value greater than F table 1% and 5%. The range of water temperature during the study was between 30°C, the water pH ranged from 7.5-8.1, DO ranged from 4.2 to 4.5 ppm and the water salinity during the study was 15-20 ppt. The result of statistical analysis showed that the treatments has significant influence to the growth of fish with F count greater than F table.